2004
DOI: 10.1128/jb.186.18.6093-6100.2004
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Chloro-β-Hydroxytyrosine, a Nonproteinogenic Amino Acid of the Peptidic Backbone of Glycopeptide Antibiotics

Abstract: The role of the putative P450 monooxygenase OxyD and the chlorination time point in the biosynthesis of the glycopeptide antibiotic balhimycin produced by Amycolatopsis balhimycina were analyzed. The oxyD gene is located directly downstream of the bhp (perhydrolase) and bpsD (nonribosomal peptide synthetase D) genes, which are involved in the synthesis of the balhimycin building block ␤-hydroxytyrosine (␤-HT). Reverse transcriptase experiments revealed that bhp, bpsD, and oxyD form an operon. oxyD was inactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
84
0
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 33 publications
0
84
0
7
Order By: Relevance
“…7, the chlorination event is arbitrarily shown to occur at the end. Previous studies have shown that chlorination takes place sometime during peptide synthesis (32).…”
Section: Vol 77 2011 Map Of Occidiofungin Of B Contaminans Ms14 6195mentioning
confidence: 99%
See 1 more Smart Citation
“…7, the chlorination event is arbitrarily shown to occur at the end. Previous studies have shown that chlorination takes place sometime during peptide synthesis (32).…”
Section: Vol 77 2011 Map Of Occidiofungin Of B Contaminans Ms14 6195mentioning
confidence: 99%
“…The biosynthesis of polyketides shares striking architectural and organizational similarities with nonribosomal peptide biosynthesis, and their modules can be integrated to produce the hybrid NRPS-PKS products. Some pharmaceutical antimicrobial agents, such as the precursor of penicillin and erythromycin, are synthesized through these mechanisms (6,7,32,40).…”
mentioning
confidence: 99%
“…The role of the fourth P450 in the vancomycin gene cluster, OxyD, has been investigated in vivo, where it has been shown to be involved in the biosynthesis of L-␤-R-hydroxytyrosine (L-3-R-hydroxytyrosine), an essential precursor in the biosynthesis of the vancomycin aglycone (19,20). OxyD has been shown to be transcribed along with two other genes, the first a non-ribosomal peptide synthase (BpsD), composed of single adenylation (A) and carrier protein (PCP) domains (21), whereas the second (Bhp) was originally annotated as a perhydrolase (20) but was recently shown to be a thioesterase (22).…”
mentioning
confidence: 99%
“…However, the natural substrate of BhaA and, therefore, the timing of the two halogenation reactions have remained elusive. Feeding studies with nonchlorinated ␤-OH-Tyr indicated the biosynthesis of completely chlorinated balhimycin by a mutant strain, which is blocked in ␤-OH-Tyr synthesis (97). This fact clearly points to a chlorination time point later than the stage of free ␤-OH-Tyr.…”
Section: Halogenation Of Electron-rich Aromatic Rings and Unactivatedmentioning
confidence: 99%
“…The respective genes encoding halogenases are embedded in many NRPS and PKS biosynthetic gene clusters (33,36,78,93,98). Studies with chlorination-deficient mutants of the balhimycin producer Amycolatopsis mediterranei demonstrated that a single halogenase BhaA is responsible for the chlorination of the two ␤-OH-Tyr residues of the glycopeptide (97). BhaA is a representative of the FADH 2 -dependent halogenases, which mainly carry out halogenation of electronrich aromatic rings (61,146).…”
Section: Halogenation Of Electron-rich Aromatic Rings and Unactivatedmentioning
confidence: 99%